Peroxisome proliferator-activated receptor gamma (PPARγ) agonist fails to overcome trans-10, cis-12 conjugated linoleic acid (CLA) inhibition of milk fat in dairy sheep - Sandri E.C.* (2018)
© 2017 The Animal Consortium.The trans-10, cis-12 conjugated linoleic acid (CLA) causes milk fat depression by downregulating expression of genes and transcription factors involved in lipogenesis and it has been proposed that peroxisome proliferator-activated receptor gamma (PPARγ) can be inhibited by trans-10, cis-12 CLA. The PPARγ is a nuclear receptor activated by natural or synthetic ligands and promotes expression of lipogenic genes and its effect on mammary lipogenesis and the interaction with trans-10, cis-12 CLA in lactating ewes was evaluated using thiazolidinedione (TZD), a chemical PPARγ agonist. A total of 24 lactating ewes were randomly assigned to one of the following treatments for 7 days: (1) Control (5 ml/day of saline solution); (2) TZD (4 mg/kg of BW/day in 5 ml of saline solution); (3) CLA (27 g/day with 29.9% of trans-10, cis-12); (4) TZD+CLA. Compared with Control, milk fat content was not changed by TZD, but was decreased 22.3% and 20.5% by CLA and TZD+CLA treatments. In the mammary gland, TZD increased PPARγ gene expression by 174.8% and 207.8% compared with Control and TZD+CLA treatments, respectively. Conjugated linoleic acid reduced sterol regulatory element-binding transcription protein 1 (SREBP1) gene expression 89.2% and 75.3% compared with Control and TZD+CLA, respectively, demonstrating that TZD fails to overcome CLA inhibition of SREBP1 signaling. In adipose tissue, the expression of SREBP1 and stearoyl CoA desaturase 1 (SCD1) genes were increased by the TZD+CLA treatment, compared with the other treatments. Conjugated linoleic acid decreased milk fat concentration and expression of lipogenic genes, while TZD had no effect on milk fat concentration, expression of lipogenic enzymes or regulators in the mammary gland and failed to overcome the inhibition of these by CLA. Therefore, CLA inhibition of milk fat synthesis was independent of the PPARγ pathway in lactating dairy ewes.